2006
DOI: 10.1136/jcp.2005.034629
|View full text |Cite
|
Sign up to set email alerts
|

The predicting role of substance P in the neoplastic transformation of the hypoplastic bone marrow

Abstract: The presence of substance P in B lymphocytes of hypoplastic bone marrow may predict its neoplastic transformation. A marked correlation between substance P-positive bone marrow pattern and the expansion of tumour cells may prove the potential value of this oligopeptide in the pathogenesis of leukaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…We found both membranous and cytoplasmic SP immunoreactivity, which can be explained on the basis of NK1R internalization 6 . Cytoplasmic reactivity has also been reported in lymphocytes of children who go on to develop acute lymphoblastic leukaemia 7 . The ubiquitous presence of SP in laryngeal tumours may represent a common mechanism of tumour progression.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…We found both membranous and cytoplasmic SP immunoreactivity, which can be explained on the basis of NK1R internalization 6 . Cytoplasmic reactivity has also been reported in lymphocytes of children who go on to develop acute lymphoblastic leukaemia 7 . The ubiquitous presence of SP in laryngeal tumours may represent a common mechanism of tumour progression.…”
supporting
confidence: 63%
“…In fact, an intriguing question is why some lymphocytes in normal mucosa express SP, whereas those in metastatic lymph nodes do not. We propose a SP link between chronic mucosal inflammation and cancer, with submucosal lymphocytes secreting SP, as has been described in neoplastic lymphocytes 7 …”
mentioning
confidence: 61%
“…doi:10.1371/journal.pone.0009690.g003 Our data do not rule out the possibility of NGF or BDNF acting on gene expression in BMSC through one, or several, intermediate factors. Increased expression or release of Substance-P following neurotrophic stimulation of cells has been described in diverse settings documenting its important role in the hematopoieticneuro-immune axis in inflammation, as well as normal and malignant hematopoiesis [57][58][59][60][61][62]. Relevant to our model, Substance-P has been shown to participate in upregulation of .…”
Section: Discussionmentioning
confidence: 55%
“…79 80 The results prompted us to perform analogous phenotyping of the material sampled from patients with clinical symptoms of BM hypoplasia. 95 In some, the proportion of SP-positive cells among all nucleated cells amounted to 67.6-95.8% (mean 81.5% cells for immunocytochemistry and 84.3% with in situ hybridisation) in the absence of neoplastic cells. Subsequent observation of these patients showed that they developed a proliferative disease of the BM.…”
Section: Leukaemiamentioning
confidence: 96%
“…Thus, SP might accelerate the already initiated development of leukaemia. 95 The origin of leukaemia, however, seems to be independent of SP expression. 96 The expression of SP in apparently normal BM lymphocytes before their neoplastic transformation could not predict death of the patient; this was related to the insufficient number of patients with neoplastic transformation and to different chemotherapy protocols used in the treatment of ALL and acute non-lymphocytic leukaemia.…”
Section: Leukaemiamentioning
confidence: 99%